Subunits of the Drosophila actin-capping protein heterodimer regulate each other at multiple levels - Amândio, Ana Rita (2015)
The actin-Capping Protein heterodimer, composed of the α and β subunits, is a master F-actin regulator. In addition to its role in many cellular processes, Capping Protein acts as a main tumor suppressor module in Drosophila and in humans, in part, by restricting the activity of Yorkie/YAP/TAZ oncogenes. We aimed in this report to understand how both subunits regulate each other in vivo. We show that the levels and capping activities of both subunits must be tightly regulated to control F-actin levels and consequently growth of the Drosophila wing. Overexpressing capping protein α and β decreases both F-actin levels and tissue growth, while expressing forms of Capping Protein that have dominant negative effects on F-actin promote tissue growth. Both subunits regulate each other's protein levels. In addition, overexpressing one of the subunit in tissues knocked-down for the other increases the mRNA and protein levels of the subunit knocked-down and compensates for its loss. We propose that the ability of the α and β subunits to control each other's levels assures that a pool of functional heterodimer is produced in sufficient quantities to restrict the development of tumor but not in excess to sustain normal tissue growth.